Environmental forensics - Hester, R. E.; Harrison, Roy M., 1948- (Issues in environmental science and technology ;, 2008)
Environmental forensics' is a combination of analytical and environmental chemistry, which is useful in the court room context. It therefore involves field analytical studies and both data interpretation and modelling connected with the attribution of pollution events to their causes. Recent decades have seen a burgeoning of legislation designed to protect the environment and, as the costs of environmental damage and clean-up are considerable, not only are there prosecutions by regulatory agencies, but the courts are also used as a means of adjudication of civil damage claims relating to envir.